Operationalising the Capability Approach: A German Correlation Sensitive Poverty Index - Nicole Rippin (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
The official measure to analyse poverty in Germany is the at-risk-of-poverty rate, defined as 60 per cent of the median net equivalence income. The severe methodological weaknesses of this rate seem to be the main source for the uncertainty that the issue of poverty in Germany generates in the minds of both the government and the public. Especially since it smacks of envy as a person needs more when others have more. The unacceptance of the rate is additionally fuelled by the high figures it produces. This paper uses the rich data source of the German Socio-Economic Panel in order to propose a new multidimensional poverty index for Germany that is based on the capability approach. It also introduces a multidimensional happiness index, a concept that is enjoying increasing popularity. All three indices are compared across dimensions, regions and over time, and the results seem to indicate one thing above all: the high added value that is created though the new German Correlation Sensitive Poverty Index (GCSPI).
Keywords: I32; 330; Multidimensional poverty measurement; counting indices; inequality; correlation sensitivity; identification